Customs and Traditions and their Role in Revealing the Purposes of Islamic law - Daradkh, Ayman Eleyyan Ahmed (Journal of Islamic Sciences, 2021)
This research studies Customs and Traditions and their relationship with the objectives of Islamic law. It has been divided into three sections, the first: concepts and terms of the study, the second: customs and their relationship to the method of reasoning and worship in Islamic law. And the third: customs and their relationship to interests and evils. The research tried to answer the following questions: What is the role of custom in achieving the intention of the street? What is the relationship between custom and the purposes of Sharia? The researcher has concluded that there is a relationship between custom and the purposes of Sharia, and the role of custom in achieving the intention of the street, considering that the interest is usually one of the customs, and it has been proven that the lawmaker has taken into account the interests of people, and among them is the consideration of their customs in legislation, and therefore the jurist must observe custom and custom In the ruling, in line with the realization of the street’s intent.